A crise da representação na linguagem no século XX: uma análise crítica a partir da semiótica de Charles S. Peirce - OTÁVIO DE LIMA E SILVA (2022)
This research brings to light a controversial issue in contemporary philosophy, namely, the crisis of representation, from the perspective of language. At the beginning of the 20th century, a very rich field was opened for the performance of a nascent and very fruitful science, semiotics, in particular Peircean Semiotics, as a tool for reading and analyzing signs. According to Santaella and Nöth, many are the philosophers, after Peirce, who announce a “crisis of representation” in language, such as Heidegger, Adorno, Lukács and Lyotard. Several crises are presented, such as the crisis of fundamentals, of grand narratives, the crisis of reason, of European sciences, of the subject, of art and, within language studies, of representation. First, we will expose the reader to Peirce's philosophy, his Pragmatism, his Phenomenology and his Semiotics, so that, in possession of a realistic notion of the sign, we can face the defenders of the crisis of representation. Secondly, we analyze Michel Foucault's postulates presented in As palavras e as coisas, for their particular semiotic interest; in this text, he focuses on the history of knowledge forging an “archaeology of knowledge”, identifying a rupture in the ternary sign models, which became dyadic from Port-Royal (XVII-XVIII) to Saussure's structuralism in the twentieth century. From the Foucaultian point of view, representation, in the raditional molds, enters into crisis, no longer speculating — in the sense of reflecting a description of nature — and becomes structural, breaking the link between sign and reality, where we will respond with Peircean Semiotics. However, there are more radical theories, such as the deconstruction of representation in Derrida. We will present Derrida's theses, who defends an impossibility of representation, and then we will make a critical analysis of his case in the light of Peirce's Semiotics, in order to expose one of the later developments of Peirce's thought on this problem. Is there a crisis of representation in language? This is what Peircean Semiotics, in this dissertation, intends to answer.